Paulus als Erzähler? Eine narratologische Perspektive auf die Paulusbriefe - Heilig, Christoph (De Gruyter, 2020)
In recent Pauline research, the critical importance of implicit narratives for understanding the apostle s Epistles gained importance. The study examines this in a critical analysis using narrative theory and text linguistics. Heilig s text analysis lines out a new narratological approach to Pauline exegesis.
German
Keywords: discourse analysis; text grammar; Text types; narratology